2007
DOI: 10.1038/sj.emboj.7601636
|View full text |Cite
|
Sign up to set email alerts
|

The dependence receptor Ret induces apoptosis in somatotrophs through a Pit-1/p53 pathway, preventing tumor growth

Abstract: Somatotrophs are the only pituitary cells that express Ret, GFRα1 and GDNF. This study investigated the effects of Ret in a somatotroph cell line, in primary pituitary cultures and in Ret KO mice. Ret regulates somatotroph numbers by inducing Pit‐1 overexpression, leading to increased p53 expression and apoptosis, both of which can be prevented with Ret or Pit‐1 siRNA. The Pit‐1 overexpression is mediated by sustained activation of PKCδ, JNK, c/EBPα and CREB induced by a complex of Ret, caspase 3 and PKCδ. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(121 citation statements)
references
References 53 publications
3
112
3
3
Order By: Relevance
“…The observation that RET is involved in both cancer progression and nervous system development, similar to previously identified DRs, led to the question as to whether it could also be one of them. It was then shown that, in different settings, expression of RET induced apoptosis in the absence, but not in the presence, of glial cell line-derived neurotrophic factor (Bordeaux et al, 2000;Canibano et al, 2007).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…The observation that RET is involved in both cancer progression and nervous system development, similar to previously identified DRs, led to the question as to whether it could also be one of them. It was then shown that, in different settings, expression of RET induced apoptosis in the absence, but not in the presence, of glial cell line-derived neurotrophic factor (Bordeaux et al, 2000;Canibano et al, 2007).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…In contrast to its well-established role as an oncogene for several cancer types, RET has been recently proposed to play tumor suppressor roles in colorectal cancer (CRC) and pituitary adenoma [46,47]. Such tumor suppressor role might be functionally linked to a pro-apoptotic role exerted by RET by behaving as a "dependence" receptor [48].…”
Section: Ret As a Tumor Suppressormentioning
confidence: 99%
“…When stimulated by GDNF, it behaved as as an oncogene able to activate intracellular signaling and cell survival. Instead, in the absence of GDNF, RET behaved as a tumor suppressor; caspase-mediated RET processing induced Pit-1 expression, that, in turn, caused p19Arf and p53 upregulation and apoptosis [46,49].…”
Section: Ret As a Tumor Suppressormentioning
confidence: 99%
“…This promotes RET cleavage, leading finally to p53 expression and apoptosis (Canibano et al, 2007). In the case of ErbB2, it has been shown that the fragment generated through the caspase-dependent cleavage contains a BH3-like domain involved in its mitochondrial localization and its association with the anti-apoptotic protein, Bcl-x L .…”
Section: Both Survival Receptors and Messengers Of Deathmentioning
confidence: 99%